Highly enhanced electromechanical properties of PVDF-TrFE/SWCNT nanocomposites using an efficient polymer compatibilizer. (22nd March 2018) - Cho, Kie Yong; Park, Hyunchul; Kim, Hyun-Ji; Do, Xuan Huy; Koo, Chong Min; Hwang, Seung Sang; Yoon, Ho Gyu; Baek, Kyung-Youl
Abstract: PVDF-TrFE/SWCNT nanocomposites with outstanding electromechanical properties were produced using P3HT-PMMA block copolymers as a compatibilizer between PVDF-TrFE and SWCNT. P3HT-PMMA block copolymer coated SWCNT (PTMCNT) was first prepared to utilize π-π stacking interactions between SWCNT and the P3HT block segment. The obtained PTMCNTs are highly compatible with the PVDF-TrFE matrix due to strong hydrogen bonding interaction between the polymer matrix and the PMMA block segment on the surface of SWCNT, leading to a very low percolation behavior at 0.05 wt% of SWCNT in PVDF-TrFE. The obtained electroactive PVDF-TrFE/SWCNT nanocomposites showed ca. 50 times increased electromechanical thickness strain, ca. 3200 times increased elastic energy density, and ca. 460 times increased electrical-to-mechanical energy conversion rate in comparison to those of pristine PVDF-TrFE at the relatively low electric field (50 Vpp μm-1). These outstanding properties result from the ultra-low percolation of SWCNT along with uniform local field distribution in PVDF-TrFE, which kept not only intrinsic properties of PVDF-TrFE such as all-trans formed crystalline phase and softness but also enhanced electrical properties including dielectric constant. Graphical abstract: Image 1